Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/en13092289
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Location-Reallocation of Battery Energy Storage Systems in DC Microgrids

Abstract: This paper deals with the problem of optimal location and reallocation of battery energy storage systems (BESS) in direct current (dc) microgrids with constant power loads. The optimization model that represents this problem is formulated with two objective functions. The first model corresponds to the minimization of the total daily cost of buying energy in the spot market by conventional generators and the second to the minimization of the costs of the daily energy losses in all branches of the network. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The main advantage of this approach is that the global optimal solution is guaranteed via second-order cone optimization, applied to a study case using real-time simulations. The authors in [16] have proposed a MINLP model for optimal location and reallocation of battery energy storage systems in DC grids to reduce the daily energy losses and the total energy purchasing costs in the conventional sources. Numerical results demonstrated that the location of the batteries is dependent on the performance index used as the objective function, i.e., energy losses or energy purchasing costs; in this sense, authors have demonstrated a multi-objective compromise between both objectives.…”
Section: Brief Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of this approach is that the global optimal solution is guaranteed via second-order cone optimization, applied to a study case using real-time simulations. The authors in [16] have proposed a MINLP model for optimal location and reallocation of battery energy storage systems in DC grids to reduce the daily energy losses and the total energy purchasing costs in the conventional sources. Numerical results demonstrated that the location of the batteries is dependent on the performance index used as the objective function, i.e., energy losses or energy purchasing costs; in this sense, authors have demonstrated a multi-objective compromise between both objectives.…”
Section: Brief Literature Surveymentioning
confidence: 99%
“…It is worthy to mention that the model of the optimal power flow in DC grids is also non-linear and non-convex due to the product between voltage variables in the power balance constraint, which makes necessary to use specialized software (i.e., GAMS) to solve it efficiently [16].…”
Section: Power Balance Constraintmentioning
confidence: 99%
“…The PF has been widely studied in the past decades on AC networks [8][9][10]. However, concerning power-flow analysis in DC grids, the exploration of this problem started recently due to the paradigm shift regarding energy distribution with renewable energy and batteries, which typically operate with DC technologies [11][12][13][14][15][16]. These technologies are currently under development.…”
Section: General Contextmentioning
confidence: 99%
“…Finally, aiming at reducing the convergence error associated with the voltage profiles, we propose an iterative version of Equation (13) in Equation (14), which is obtained by replacing v 0 d with v t d (i.e., the value of v d in iteration t) and adding some terms.…”
Section: Taylor-series-based Approximation (Tbm)mentioning
confidence: 99%
“…References [17] and [18] have proposed convex optimization models to place and size distributed generators in DC grids considering conic and semidefinite approximations considering the peak load conditions. For their part, authors in [12] and [19] have presented MINLP models to operate battery energy storage systems in DC grids, and their solutions are reached with heuristic algorithms and convex reformulations. As another contribution, the authors of [9] have proposed a conic reformulation of the power flow problem for DC grids considering conic constraints by transforming the hyperbolic relation between voltages and currents in the power balance equations into conic constraints [20].…”
Section: Introductionmentioning
confidence: 99%